2000
DOI: 10.1080/00016340009169250
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of sonographic texture of the endometrium in post-menopausal bleeding a guide to further management

Abstract: Background. The purpose of this study was to assess the utility of transvaginal ultrasonography in the evaluation of endometrial morphology in addition to the standard criterion of endometrial thickness for selecting patients for endometrial sampling. Methods. Two hundred and seven consecutive cases of postmenopausal bleeding were evaluated by transvaginal ultrasound. Endometrial thickness was measured as the maximum anteroposterior thickness of the endometrium including both the anterior and posterior layers,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 10 publications
0
14
0
3
Order By: Relevance
“…Endometrial polyps, fibroids and endometrial cancer may manifest characteristic gray‐scale ultrasound morphology both at conventional ultrasound examination4–7 and at saline infusion sonography8, 9, but some research teams have found overlapping ultrasound morphology between benign and malignant endometrial lesions10, 11. Others concluded that the accuracy of transvaginal sonography in detecting endometrial cancer increases if assessment of endometrial morphology and endometrial border appearance is used in combination with endometrial thickness measurements12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…Endometrial polyps, fibroids and endometrial cancer may manifest characteristic gray‐scale ultrasound morphology both at conventional ultrasound examination4–7 and at saline infusion sonography8, 9, but some research teams have found overlapping ultrasound morphology between benign and malignant endometrial lesions10, 11. Others concluded that the accuracy of transvaginal sonography in detecting endometrial cancer increases if assessment of endometrial morphology and endometrial border appearance is used in combination with endometrial thickness measurements12, 13.…”
Section: Introductionmentioning
confidence: 99%
“…Studies examining screening methods for endometrial carcinoma in asymptomatic postmenopausal women have accepted ultrasound‐determined endometrial thickness as an indication of risk. The thickest anteroposterior diameter of the endometrium is measured during 2D ultrasound, and a cutoff value of 4 to 5 mm is considered predictive of pathologic changes [4–7]. Many trials were introduced to enhance the predictive usefulness of ultrasound for endometrial malignancy, and Sheikh et al [5] added abnormal focal echogenicity—the sign of a nonhomogenous endometrium—as a predictor of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Endometrial thickness has been used as an indicator of risk for endometrial carcinoma in asymptomatic menopausal and postmenopausal women. In 2‐dimensional (2D) ultrasound, the thickest anteroposterior diameter of the endometrium is measured using the 2 endometrial layers, and a cutoff value of 4 to 5 mm has been found to be predictive of pathologic changes [4–7]. However, the same thickness does not express the same endometrial volume in different endometria because uterine lengths may be different and endometrial irregularities may exist.…”
Section: Introductionmentioning
confidence: 99%
“…The morphology of the endometrium on transvaginal ultrasound is also useful in the assessment of patients with abnormal bleeding. Adding morphologic characteristics to the assessment and categorizing the endometrium as homogeneous with focally increased echogenicity, diffusely increased echogenicity, or diffusely inhomogeneous increased the specificity and negative predictive value of sonography [91].…”
Section: Imaging Of Endometrial Carcinoma In Diabetic Patientsmentioning
confidence: 99%